2018
DOI: 10.15237/gida.gd17055
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effect of Turkish Chestnut Bee Pollen on Dna Oxidation System and Its Phenolic Compounds

Abstract: Chestnut bee pollen is a high antioxidative natural bee product. In this study the phenolic compounds in chestnut bee pollen were determined by HPLC-DAD system. Ethanol, water and methanol were used for the extraction of antioxidant compounds from chestnut bee pollen. The total phenolic contents and antioxidant capacities of extracts were determined by Folin-Ciocalteu, CHROMAC (Cr(VI) reduction antioxidant capacity) and FRAP (ferric reducing antioxidant power) methods, respectively. When compared the amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Data of TP content are in agreement with previous data for raw chestnut [53,63,64]. It is well known as polyphenol content in fruit is strictly influenced by environmental conditions [65,66]. However, in this work, plants were grown in the same microclimate conditions (soil, temperature, humidity, and light) and then the difference in TP content is attributable to the cultivar genetic background.…”
Section: Differences On Carbohydrate Phenol Content and Total Antioxi...supporting
confidence: 89%
“…Data of TP content are in agreement with previous data for raw chestnut [53,63,64]. It is well known as polyphenol content in fruit is strictly influenced by environmental conditions [65,66]. However, in this work, plants were grown in the same microclimate conditions (soil, temperature, humidity, and light) and then the difference in TP content is attributable to the cultivar genetic background.…”
Section: Differences On Carbohydrate Phenol Content and Total Antioxi...supporting
confidence: 89%
“…Yesiltas et al (2014) indicated that total phenolic content of 9 bee pollen samples collected from different regions of Turkey was 12.0-36.7 mg GAE/g) and antioxidant capacities of the samples according to ABTS, CUPRAC, DPPH, and FRAP methods were 15.2-33.6 mg TE/g, 20.7-89.4 mg TE/g, 5.7-15.2 mg TE/g, and 5.2-15.7 mg TE/g, respectively. Karkar et al (2018) reported that antioxidant capacities of chestnut bee pollen samples were 3.70-34.18 mg TE/g, 3.15-20.24 mM TE/g by CHROMAC ve FRAP methods, respectively. A previous study by Anjos et al, (2019a) average total phenolic content of 6 bee pollen samples which found as predominant pollen Cistus ladanifer (42.6%) were detected 6.81 mg QE/g and average antioxidant capacity was EC50: 2.62 mg/mL by DPPH methods.…”
Section: Antioxidant Capacities and In Vitro Bioaccessibilities Of Thmentioning
confidence: 99%
“…It is currently used in the treatment of sniffles, the flu, anemia, allergic diseases and ulcer and enteritis. It is called "the life-giving dust" owing to its extensive therapeutic effects and recognized as one of the functional foods in the food industry (Borycka et al, 2015;Carpes et al, 2007;Karadal et al, 2018;Kacániová et al, 2012;Guiné, 2015;Fadzilah et al, 2017;Karkar et al, 2018;Pascoal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to a previous study, rutin was detected in a lower ratio in Cc 1 (Alimoglu et al., 2021). The highest amount of galangin was found in Ea (12.378 µg/g), whereas chestnut HBP exhibited a higher concentration (0.122 mg/g) (Karkar et al., 2018).…”
Section: Resultsmentioning
confidence: 99%